Acute pain assessments and records: a pilot study of digital transformation. (26th May 2022) - Roberts, Luke; Lanes, Sadie; Kyte, Jemma; Grady, Joanne; Holdship, Jonathan; Carey, Caroline; Cooney, Katrina; Ramessur, Suneil
Abstract : Background: Pain is a leading cause of disability worldwide. Pain assessments are an essential part of evidence-based care and management. Among comparable care providers, there is variation in how nurses document assessments as well as the content in them, and there is a notable associated administrative burden. Aims: This study evaluated the impact and significance of a new, structured, digitised pain assessment form from quality, safety and efficiency standpoints. Methods: Samples of pain assessments were examined at three consecutive stages: first, the pre-existing form was used, then the new structured form was introduced and, finally, the structured form was taken away and nurses went back to completing the original form. Assessments were scored by two clinical analysts against 18 clinically defined pain-related characteristics and factors. The time taken to extract and interpret the assessments was also recorded. Statistically significant changes were assessed using Welch's t-tests and Fisher's exact tests. Findings: There was a significant improvement in data quality using the new structured form compared with the pre-existing template, including an increase in the capture of five safety-related variables. Less time was needed to extract and interpret data with the new form. Conclusion: Intelligent structured forms are highly effective for documenting pain assessments, and offer notable benefits in quality, safety, and efficiency.